Implementation Management Based School (MBS) in School Intermediate Vocational Education in Indonesia: Systematic Literature Review - Trisnani Widowati; Clarita Apriliani; Anik Maghfiroh (Universitas Negeri Semarang, 2025)
Management Based School (MBS) is form from decentralization education that provides authority to school in the process of managing source power , retrieval decisions , and improvements quality education in a way independent . In education vocational , especially in schools Intermediate Vocational (SMK), implementation from Management Based School (MBS) is important For increase quality graduate of in accordance needs of the world of work and industry . Research This aim analyze from implementation of MBS in vocational schools in Indonesia through approach Systematic Literature Review (SLR) with study on various article scientific papers published in 2013–2025 . Study results show that MBS implementation has an impact positive to improvement quality education , effectiveness leadership head school , work The same with the industrial world , as well as on competencies graduates . However , the implementation from MBS still face challenge in the form of limitations source Power human resources (HR), low participation from society , and limitations means infrastructure . Therefore that , leadership head school , culture organization and collaboration with stakeholders to become important factors in success implementation of MBS in vocational schools.